Предмет: Алгебра, автор: safronovakarina16

Разложите на множители выражение:​

Приложения:

Ответы

Автор ответа: Universalka
1

1)a^{2}-5=a^{2}-(\sqrt{5})^{2}=(a-\sqrt{5})(a+\sqrt{5} )\\\\2)4a^{2} -7=(2a)^{2}-(\sqrt{7})^{2}=(2a-\sqrt{7} )(2a+\sqrt{7})\\\\3)\sqrt{a}+\sqrt{3a} =\sqrt{a} +\sqrt{3} *\sqrt{a}=\sqrt{a}(1+\sqrt{3})\\\\4)\sqrt{3c}-\sqrt{6c}=\sqrt{3c}-\sqrt{2} *\sqrt{3c}=\sqrt{3c}(1-\sqrt{2})\\\\5)c-11\sqrt{c}=(\sqrt{c})^{2} -11\sqrt{c}=\sqrt{c}(\sqrt{c}-11)\\\\6)\sqrt{12c}+\sqrt{28c}=\sqrt{4*3c}+\sqrt{4*7c}=2\sqrt{c}*\sqrt{3}+2\sqrt{c}*\sqrt{7}=2\sqrt{c}(\sqrt{3}+\sqrt{7})

Похожие вопросы